Stimulation of α1-adrenoceptors facilitates GABAergic transmission onto pyramidal neurons in the medial prefrontal cortex. (6th August 2015) - Luo, F.; Tang, H.; Cheng, Z.-y.
Highlights: Phenylephrine enhances GABAergic transmission onto pyramidal neurons. Phenylephrine enhances GABA release probability and number of releasable vesicles. Phenylephrine depolarizes GABAergic interneurons through the inhibition of Kirs. Abstract: Whereas activation of α1 -adrenoceptors (α1 -ARs) modulates glutamatergic transmission, the roles of α1 -ARs in GABAergic transmission in the medial prefrontal cortex (mPFC) are elusive. Here, we examined the effects of the α1 -AR agonist phenylephrine (Phe) on GABAergic transmission onto pyramidal neurons in the deep layers of the mPFC. We found that bath application of Phe dose-dependently increased the amplitude of evoked IPSCs (eIPSCs). Phe increased the frequency but not the amplitude of miniature IPSCs (mIPSCs). Ca 2+ influx through T-type voltage-gated calcium channels is required for Phe-induced increases in GABA release. Phe increases GABA release probability and the number of releasable vesicles. Phe depolarizes the fast-spiking (FS) interneurons without effects on the firing rate of action potentials (APs) of interneurons. Phe-induced depolarization is independent of extracellular Na +, Ca 2+ and T-type calcium channels, but requires inward rectifier K + channels (Kirs). The present study demonstrates that Phe enhances GABAergic transmission onto mPFC pyramidal neurons through inhibiting interneurons Kirs, which further depolarizes interneurons leading to increase in Ca 2+ influx via T-type calcium channels. Our results may provide a cellular and molecular mechanism that helps explain α1 -AR-induced PFC dysfunction.